Analysis of Students' Mathematical Representation Ability in Terms of Adversity Quotient - Tyas Rahayu Wijayani; Ipah Muzdalipah; Depi Setialesmana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study aims to describe students' mathematical representation abilities in terms of Adversity Quotient (AQ). The study used a qualitative method with a descriptive approach. Four students of grade XI MIPA MA Serba Bakti were selected purposively based on the results of the AQ questionnaire to represent the categories of Climbers, Campers–Climbers, Campers, and Quitters–Campers. The research instruments were an AQ questionnaire, a mathematical representation ability test, and a validated interview. Data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the higher the AQ category, the more complete, detailed, and correct the mathematical representation produced. Conversely, the lower the AQ category, the mathematical representation tends to be incomplete, incoherent, or produce incorrect answers. This finding confirms the relationship between AQ and mathematical representation abilities. Theoretically, this study strengthens the study of the role of non-cognitive factors in mathematics learning, while pedagogically its implications encourage teachers to consider AQ factors in designing learning strategies.